Assessment of Barriers and Enablers to Implementation of a Pediatric Early Warning System in Resource-Limited Settings - Agulnik, Asya (2022)
Importance: Pediatric early warning systems (PEWS) aid with early identification of clinical deterioration and improve outcomes in children with cancer hospitalized in resource-limited settings